Monet at a Glance: A Dynamic, Ekphrastic Encounter in Michèle Roberts’s “On the Beach at Trouville” - Goszczyńska, Marta (Text Matters: A Journal of Literature, Theory and Culture, 2022)
The essay analyzes Michèle Roberts’s 2012 story “On the Beach at Trouville” as an ekphrasis of Claude Monet’s early Impressionist painting, The Beach at Trouville. It first approaches the narrative though W. J. T. Mitchell’s model in which ekphrasis is understood as staging “a war of signs,” only to conclude that the dynamics between the painting and the story is too complex to be satisfactorily explained in these terms. As a result, the essay moves on to read the story as an “ekphrastic encounter” and uses Norman Bryson’s concept of the glance to account for what happens between Roberts’s text and Monet’s image. Bryson discusses the glance in opposition to the totalizing, immobile and disembodied gaze and understands it both as a way of looking and painting. The essay reveals how the glance can be used to explain important dimensions of Roberts’s ekphrastic project: its depiction of Monet’s picture as a semiotic system of arbitrary signs, its emphasis on the durational, performative aspect of painting, its insistence on the contingent nature of interpretation, and, finally, its attempts to mimic Monet’s Impressionist style. All these features, the essay argues, allow Roberts to transform her story into a dynamic scene of intermedial dialogue where word and image enter a relation of what Stephen Scobie describes as “reciprocal supplementarity.”